Trinidad, native house - Payne (Davidson and Todd Ltd., Trinidad, 2010)
A man stands next to a wooden frame hut on stilts with a thatched roof.
Colour: Coloured (Handpainted) Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Wooden-frame houses; Huts